2017
DOI: 10.5530/ijper.51.2s.52
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Carbamazepine Liquisolid Compacts Using Novel Carriers

Abstract: Objective: The aim of present investigation was to prepare liquisolid compacts of high dose water insoluble drug, carbamazepine (CBZ) using novel porous carriers such as Neusilin and Fujicalin in order to improve its dissolution rate and reduce the tablet weight. Materials and Methods: Solubility of CBZ was determined in different non volatile solvents to finalise vehicle having maximum solubility. The liquid retention potential (ф) of carriers and coating material was determined and 18 different liquisolid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…9 and 10, there is a reduction in intensity of the characteristic absorption bands of drug in liquisolid formulations which might be attributed to the hydrogen bonding interaction of the amin group of lacidipine with the hydroxyl group of the PEG 200. This resulted in drug dissolution enhancement as shown by dissolution data [34]. …”
Section: Fourier-transform Infrared Spectroscopy (Ftir)mentioning
confidence: 89%
See 1 more Smart Citation
“…9 and 10, there is a reduction in intensity of the characteristic absorption bands of drug in liquisolid formulations which might be attributed to the hydrogen bonding interaction of the amin group of lacidipine with the hydroxyl group of the PEG 200. This resulted in drug dissolution enhancement as shown by dissolution data [34]. …”
Section: Fourier-transform Infrared Spectroscopy (Ftir)mentioning
confidence: 89%
“…From the result, it is concluded that concentration of drug in liquid medication is an important factor in drug release [33]. A decrease in concentration of drug in PEG 200 increases the dispersion of drug at molecular level which may further enhance the dissolution rate of the drug [34].…”
Section: In Vitro Drug Dissolution Studiesmentioning
confidence: 99%
“…The drug concentration in each solution was analyzed by UV spectrophotometer at 210 nm. 15 Preparation of Liquisolid Compacts: Ramipril liquisolid systems were prepared and compressed into tablets of 20 mg strength each, using a single punching machine with the aim of the desired hardness of 3-6 kg/cm 2 . All liquisolid formulations contained microcrystalline cellulose as the carrier powder and silica as the coating material at a fixed powder excipient ratio (R) of 20.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, there is no undesired interaction between the drug and excipients. It can be noticed a reduction in intensity of the characteristic absorption bands of the drug in liquisolid formulations which might be attributed to the hydrogen bonding interaction of the amino and carboxyl group of furosemide with the hydroxyl group of the liquid vehicles PEG 400 [45].…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%